1981
DOI: 10.1007/bf00431099
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuroleptic treatment of chronic schizophrenic patients: Clinical and biochemical effects of withdrawal

Abstract: In 17 chronic schizophrenic patients under chronic neuroleptic treatment for 13 years, a 30-day drug withdrawal resulted in early relapse of four patients, slight deterioration in five, and slight amelioration in eight patients. No incidence of neuroleptic symptoms such as tardive dyskinesia occurred. Prolactin in plasma and cerebrospinal fluid (CSF), not being elevated under chronic treatment, decreased significantly after 30 days of withdrawal. Homovanillic acid and 3-methoxy-4-hydroxyphenylglycol in CSF ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Analysis of uri nary catecholamines is a reliable means of assessing sym pathoadrenal function in schizophrenic patients [37], We recorded a decrease in urinary epinephrine and norepi nephrine excretion during the therapeutic suspension phase, primarily in cases where baseline values under the preceding haloperidol intake had been elevated. After long-term neuroleptic intake, too, serum norepinephrine levels fell only if the respective values before discontinua tion had been distinctly elevated [4,25], A significant decrease in VMA -the main metabolite of norepineph rine and representative of the norepinephrine metabolism [38] -after discontinuation of neuroleptic therapy was also detected in our study only if baseline values were ele vated.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Analysis of uri nary catecholamines is a reliable means of assessing sym pathoadrenal function in schizophrenic patients [37], We recorded a decrease in urinary epinephrine and norepi nephrine excretion during the therapeutic suspension phase, primarily in cases where baseline values under the preceding haloperidol intake had been elevated. After long-term neuroleptic intake, too, serum norepinephrine levels fell only if the respective values before discontinua tion had been distinctly elevated [4,25], A significant decrease in VMA -the main metabolite of norepineph rine and representative of the norepinephrine metabolism [38] -after discontinuation of neuroleptic therapy was also detected in our study only if baseline values were ele vated.…”
mentioning
confidence: 68%
“…Data on the predic tive value of serum prolactin for the clinical effect of sub sequent neuroleptic withdrawal in chronic schizophrenic patients are divergent: Some authors [5,25,[29][30][31] found no statistically significant correlation between prolactin levels and psychopathological changes after neuroleptic withdrawal. In contrast, others [4,6,32,33] reported that patients with an unfavorable withdrawal effect (rapid relapse) have lower baseline prolactin levels than patients with a more favorable withdrawal effect. It is concluded from these data that the dopamine-blocking effect of neu roleptics is less marked, at least functionally, in these patients than in patients with a more favorable withdraw al effect, i.e.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The most promising of these are measures of central nervous system (CNS) dopamine (DA) activ ity including plasma prolactin levels (PRL) (Brown et al 1981;Zander et al 1981;Wistedt et al 1982;Lieber man et al 1986a), growth hormone response to DA agonist stimulation (Cleghorn et al 1983;Mueller Spahn et al 1984;Lieberman et al 1986), plasma neu roleptic levels (Brown et al 1982;Brown et al 1985;Marder et al 1987), pHV A (Davidson et al 1991) and behavioral response to DA agonist stimulation (van Kammen et al 1982;Davidson et al 1987;Lieberman et al 1987b;Angrist et al 1981). The latter line of inves tigation is based on the fi.nding originally demonstrated by Janowsky et al (1973) and Angrist et al (1980) that a single or brief administration of a DA agonist can in duce psychotic symptoms in schizophrenics in doses that would not induce psychosis in normal subjects (Lie berman et al 1987a).…”
mentioning
confidence: 99%